Rethinking scientific responsibility. Issue 5 (25th January 2011) - Forssén, Annika; Meland, Eivind; Hetlevik, Irene; Strand, Roger
Abstract : Researchers should be made co-responsible for the wider consequences of their research focus and the application of their findings. This paper describes a meta-reflection procedure that can be used as a tool to enhance scientific responsibility and reflective practice. The point of departure is that scientific practice is situated in power relations, has direction and, consequently, power implications. The contextual preconditions and implications of research should be stated and discussed openly. The reflection method aims at revealing both upstream elements, such as for instance preconceptions, and downstream elements, for example, public consequences of research. The validity of research might improve from such discussions. Validity should preferably be understood as a broader concept than the methodological concerns in science.